Pseudorabies virus glycoprotein gIII is a major target antigen for murine and swine virus-specific cytotoxic T lymphocytes. - Zuckermann, F A (1990)
Pseudorabies virus (PrV) is the etiological agent of Aujeszky's disease, a disease that causes heavy economic losses in the swine industry. A rational approach to the generation of an effective vaccine against this virus requires an understanding of the immune response induced by it and of the role of the various viral antigens in inducing such a response. We have constructed mutants of PrV [strain PrV (Ka)] that differ from each other only in expression of the viral nonessential glycoproteins gI, gp63, gX, and gIII (i.e., are otherwise isogenic). These mutants were used to ascertain the importance of each of the nonessential glycoproteins in eliciting a PrV-specific cytotoxic T-lymphocyte (CTL) response in mice and pigs. Immunization of DBA/2 mice and pigs with a thymidine kinase-deficient (TK-) mutant of PrV elicits the formation of cytotoxic cells that specifically lyse syngeneic infected target cells. These PrV-specific cytolytic cells have the phenotype of major histocompatibility complex class I antigen-restricted CTLs. The relative number of CTLs specific for glycoproteins gI, gp63, gX, and gIII induced in mice vaccinated with a TK- mutant of PrV was ascertained by comparing their levels of cytotoxicity against syngeneic cells infected with either wild-type virus or gI-/gp63-, gX-, or gIII- virus deletion mutants. The PrV-specific CLTs were significantly less effective in lysing gIII(-)-infected targets than in lysing gI-/gp63-, gX-, or wild-type-infected targets. The in vitro secondary CTL response of lymphocytes obtained from either mice or pigs 6 or more weeks after immunization with a TK- mutant of PrV was also tested. Lymphocytes obtained from these animals were cultured with different glycoprotein-deficient mutants of PrV, and their cytolytic activities against wild-type-infected targets were ascertained. The importance of each of the nonessential viral glycoproteins in eliciting CTLs was assessed from the effectiveness of each of the virus mutants to stimulate the secondary anti-PrV CTL response. Cultures of both murine or swine lymphocytes that had been stimulated with gIII- virus contained only approximately half as many lytic units as did those stimulated with either wild-type virus, a gX- virus mutant, or a gI-/gp63- virus mutant. Thus, a large proportion of the PrV-specific CTLs that are induced by immunization with PrV of both mice and pigs are directed against gIII. Furthermore, glycoproteins gI, gp63, and gX play at most a minor role in the CTL response of these animals to PrV.